PENGARUH FRAKSI EKSTRAK DAUN PACAR CINA (AGLAIA ODORATA L.) TERHADAP PERTUMBUHAN COLLETOTRICHUM CAPSICI PENYEBAB PENYAKIT ANTRAKNOSA PADA CABAI (CAPSICUM ANNUUM L.) SECARA IN VITRO - ., Efri; Aeny, Titik Nur; Maryono, Tri; Ronalddi, Eko (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Influence of Aglaia odorata L. leaf extract on in vitro growth of chilli antrachnose fungi (Colletotrichum capsici). Pacar cina (Aglaia odorata L.) is known as one of the potential herbs as fungicides. The objective of this study was to determine The effectiveness of various leaf extract fractions of pacar cina as a fungicide to suppress the in vitro growth of C. capsici, The causal agent of anthracnose disease on chili. This study consisted of two sub-experiments. The first experiment consisted of 12 treatments: leaf extract fractions with distilled water solvent, leaf extract fractions with ethanol solvent with a concentration of 10, 20, 30, 40, 50, 60, 70, 80 and 90%, propineb 0.2 % (synthetic fungicides) and control (without fungicide). The Second experiment consisted of 12 treatments: leaf extract fractions with distilled water solvent, leaf extract fractions with the solven of n-hexane at a concentration of 10, 20, 30, 40, 50, 60, 70, 80 and 90%, propineb 2% (synthetic fungicides), and control (without fungicides). The treatmentswerearranged by completely randomized design (CRD) with three replications. Variables measured in this experiment were colony diameter and density of spores of C. capsici. Data were analyzed by analysis of variance (ANOVA) and differences between the mean values was tested by Duncan Multiple Range Test (DMRT) with the level of 5% significant different. Additionally, leaf extract that effectively inhibited the growth of C. capsici was the fraction of the leak extract with 80% ethanol solvent and 10%, 60%, and 90% n-hexanesolvent. The result showed that the leaf extract fraction of pacar cina was potentially used as fungicide to inhibit the growth of C. capsici.